Functional dynamics of human ubiquitin C-terminal hydrolases - Puri, Sarita; Hsu, Shang-Te Danny (Frontiers in Biophysics, 2024)
Ubiquitin C-terminal hydrolases (UCHs) are crucial enzymes within the ubiquitin-proteasome system, characterized by a characteristic Gordian knotted topology. Another important structural feature of the UCH family is a hydrophobic β-sheet core containing a conserved catalytic triad of cysteine, histidine, and aspartate wrapped by several α-helices and a crossover loop. The catalytic triad cleaves the (iso)peptide bond at the C-terminus of ubiquitin via a nucleophilic attack. The highly dynamic crossover loop is involved in substrate binding and selectivity. UCHs play vital roles in various cellular processes, such as cell signaling, DNA repair, neuroprotection, and tumor suppression. Point mutations in catalytic and noncatalytic residues of UCHs are linked to various diseases, including cancers and neurodegeneration. Additionally, post-translational modifications (PTMs), such as oxidation, impact the deubiquitinase activity of UCHs and increase aggregation propensity. This review focuses on how disease-associated point mutations, PTMs, and interactions with different binding partners modulate the structural and functional dynamics of UCHs and how perturbations of these functional dynamics are characterized using a battery of biophysical techniques to gain insights into the molecular mechanisms underlying UCH dysfunction and diseases.